Modulation of SIV and HIV DNA Vaccine Immunity by Fas-FasL Signaling - Yan, Jiabin; Zapata, Juan; Pauza, Charles; Salvato, Maria (Viruses, 2015)
Signaling through the Fas/Apo-1/CD95 death receptor is known to affect virus-specific cell-mediated immune (CMI) responses. We tested whether modulating the Fas-apoptotic pathway can enhance immune responses to DNA vaccination or lymphocytic choriomeningitis virus (LCMV) infection. Mice were electroporated with plasmids expressing a variety of pro- or anti-apoptotic molecules related to Fas signaling and then either LCMV-infected or injected with plasmid DNA expressing SIV or HIV antigens. Whereas Fas or FasL knockout mice had improved CMI, down-regulation of Fas or FasL by shRNA or antibody failed to improve CMI and was accompanied by increases in regulatory T cells (Treg). Two “adjuvant” plasmids were discovered that significantly enhanced plasmid immunizations. The adjuvant effects of Fas-associated death domain (FADD) and of cellular FLICE-inhibitory protein (cFLIP) were consistently accompanied by increased effector memory T lymphocytes and increased T cell proliferation. This adjuvant effect was also observed when comparing murine infections with LCMV-Armstrong and its persisting variant LCMV-Clone 13. LCMV-Armstrong was cleared in 100% of mice nine days after infection, while LCMV-Clone 13 persisted in all mice. However, half of the mice pre-electroporated with FADD or cFLIP plasmids were able to clear LCMV-Clone 13 by day nine, and, in the case of cFLIP, increased viral clearance was accompanied by higher CMI. Our studies imply that molecules in the Fas pathway are likely to affect a number of events in addition to the apoptosis of cells involved in immunity.